2023
DOI: 10.1302/0301-620x.105b7.bjj-2022-0989.r1
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of arthroscopy of the hip for femoroacetabular impingement based on intraoperative assessment using the Outerbridge classification

Abstract: AimsHip arthroscopy (HA) has become the treatment of choice for femoroacetabular impingement (FAI). However, less favourable outcomes following arthroscopic surgery are expected in patients with severe chondral lesions. The aim of this study was to assess the outcomes of HA in patients with FAI and associated chondral lesions, classified according to the Outerbridge system.MethodsA systematic search was performed on four databases. Studies which involved HA as the primary management of FAI and reported on chon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 90 publications
0
0
0
Order By: Relevance
“…Prior studies have demonstrated that increased cartilage wear is associated with inferior outcomes following hip arthroscopy [26]. A recent study reported that an official diagnosis of hip osteoarthritis was associated with prolonged opioid use following hip arthroscopy [2].…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have demonstrated that increased cartilage wear is associated with inferior outcomes following hip arthroscopy [26]. A recent study reported that an official diagnosis of hip osteoarthritis was associated with prolonged opioid use following hip arthroscopy [2].…”
Section: Discussionmentioning
confidence: 99%